Skeletal muscle alterations in chronic heart failure: differential effects on quadriceps and diaphragm. Issue 4 (30th April 2015) - Mangner, Norman; Weikert, Bettina; Bowen, T. Scott; Sandri, Marcus; Höllriegel, Robert; Erbs, Sandra; Hambrecht, Rainer; Schuler, Gerhard; Linke, Axel; Gielen, Stephan; Adams, Volker
Abstract: Background: Chronic heart failure (CHF) results in limb and respiratory muscle weakness, which contributes to exercise intolerance and increased morbidity and mortality, yet the molecular mechanisms remain poorly understood. Therefore, we aimed to compare parameters of antioxidative capacity, energy metabolism, and catabolic/anabolic balance in diaphragm and quadriceps muscle in an animal model of CHF. Methods: Ligation of the left anterior descending coronary artery ( n = 13) or sham operation ( n = 11) was performed on Wistar Kyoto rats. After 12 weeks, echocardiography and invasive determination of maximal rates of left ventricular (LV) pressure change were performed. Antioxidative and metabolic enzyme activities and expression of catabolic/anabolic markers were assessed in quadriceps and diaphragm muscle. Results: Ligated rats developed CHF (i.e. severe LV dilatation, reduced LV ejection fraction, and impaired maximal rates of LV pressure change; P < 0.001). There was a divergent response for antioxidant enzymes between the diaphragm and quadriceps in CHF rats, with glutathione peroxidase and manganese superoxide dismutase activity increased in the diaphragm but reduced in the quadriceps relative to shams ( P < 0.01). Metabolic enzymes were unaltered in the diaphragm, but cytochrome c oxidase activity ( P < 0.01) decreased and lactate dehydrogenase activity ( P < 0.05) increased in the quadriceps of CHF animals. Protein expression of the E3 ligase muscle ring finger 1 and proteasome activity were increased ( P < 0.05) in both the diaphragm and quadriceps in CHF rats compared with shams. Conclusion: Chronic heart failure induced divergent antioxidative and metabolic but similar catabolic responses between the diaphragm and quadriceps. Despite the quadriceps demonstrating significant impairments in CHF, apparent beneficial adaptations of an increased antioxidative capacity were induced in the diaphragm. Nevertheless, muscle ring finger 1 and proteasome activity (markers of protein degradation) were elevated and oxidative enzyme activity failed to increase in the diaphragm of CHF rats, which suggest that a myopathy is likely present in respiratory muscle in CHF, despite its constant activation.